2011
DOI: 10.1056/nejmoa1013343
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Effect of Point Mutations in Myelodysplastic Syndromes

Abstract: BACKGROUND Myelodysplastic syndromes are clinically heterogeneous disorders characterized by clonal hematopoiesis, impaired differentiation, peripheral-blood cytopenias, and a risk of progression to acute myeloid leukemia. Somatic mutations may influence the clinical phenotype but are not included in current prognostic scoring systems. METHODS We used a combination of genomic approaches, including next-generation sequencing and mass spectrometry–based genotyping, to identify mutations in samples of bone marr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

60
1,467
7
28

Year Published

2012
2012
2016
2016

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 1,485 publications
(1,562 citation statements)
references
References 35 publications
60
1,467
7
28
Order By: Relevance
“…The latter is also the preferred treatment of choice in AML associated with FLT3-ITD, whereas chemotherapy alone might be adequate for AML patients expressing NPM1 mutations without FLT3-ITD. 1 Similarly, the prognostic relevance of mutations in myelodysplastic syndromes 2 and primary myelofibrosis (PMF) 3 has been recognized but not yet implemented in clinical practice.…”
Section: Introductionmentioning
confidence: 99%
“…The latter is also the preferred treatment of choice in AML associated with FLT3-ITD, whereas chemotherapy alone might be adequate for AML patients expressing NPM1 mutations without FLT3-ITD. 1 Similarly, the prognostic relevance of mutations in myelodysplastic syndromes 2 and primary myelofibrosis (PMF) 3 has been recognized but not yet implemented in clinical practice.…”
Section: Introductionmentioning
confidence: 99%
“…Acquired genetic lesions are frequently present in myelodysplastic syndromes (MDS) [1], with cytogenetic abnormalities noted in approximately 45% of patients at diagnosis [2]. Allogeneic stem cell transplant is potentially curative in MDS, but its utility is limited by the relatively high incidence of treatment-related mortality and morbidity [3].…”
Section: Introductionmentioning
confidence: 99%
“…6,9 Mutations in other myelodysplastic syndrome-related genes, especially TET2, ASXL1, TP53, and EZH2, were not tested in this study. 6,10 Using global profiling, we identified a list of differentially expressed plasma microRNAs in patients with myelodysplastic syndromes with different outcomes, among patients with different cytogenetic features, and between patients with myelodysplastic syndromes versus healthy individuals. For patients with a diploid karyotype and none of the common myelodysplastic syndromerelated mutations, admittedly a heterogeneous group, there are no known clinicopathologic or biologic markers that can further stratify these patients.…”
Section: Discussionmentioning
confidence: 99%
“…7,8 Alterations in apoptosis and proliferation have been implicated in the pathogenesis of myelodysplastic syndromes, and recurrent gene mutations have been associated with the disease progression and outcome. 9,10 In addition, gene expression studies have identified markers that appear to improve the accuracy of risk stratification or prognostication; 11 however, none of these markers have been included in the original or revised International Prognostic Scoring System. 12 MicroRNAs are a class of short (19-25 nucleotides), single-stranded RNA molecules that are components of the epigenetic machinery.…”
mentioning
confidence: 99%